(untitled) (Baghdad Science Journal, 2005)
Been in this gravel study the effect of Alchgag fast neutrons emitted by the source on the electrical properties of silicon solar cells monounsaturated crystal at a constant rate of neutron flow rate of a wide range of neutron flow speed ranges for periods of time ranging from 2-10 hours